The Stimulation of Entrepreneurial Activity During Wartime: The Experience of Ukraine - Bagatska, Kateryna; Bilous, Nataliia (Journal of Public Governance, 2024)
Objective: The article aims to present different governmental methods and tools for the stimulation of entrepreneurial activity in Ukraine during the full-scale war period. The purpose is to emphasise the necessity of SMEs’ governmental support due to the sharp economic decline.Research Design & Methods: The article uses secondary data analysis, desktop research, case-study method, as well as methods of analysis and synthesis.Findings: The research suggests that scholars from developed countries underline mainly indirect influence of the state support through creating a favourable environment for fostering SMEs’ growth and performance. On the contrary, scholars from developing countries with transitional economies focus mostly on the direct governmental support, which is the relevant case of Ukraine. These direct methods of support (grants, affordable loans, deregulation) have proved to be efficient since their implementing.Implications / Recommendations: This paper may be crucial for researchers of entrepreneurship development in transitional economies in crisis periods. Also, it may be useful for policymakers, whose task is to foster economic growth through SMEs.Contribution / Value Added: This paper benchmarks different approaches of developed and developing countries to the governmental support of SMEs. The article showcases the experience of Ukraine.Article classification: research articleJEL classification: H7, O52, E650